Predictive Model for Ambulatory Hypertension Based on Office Blood Pressure in Obese Children - Bhatt, Girish C.; Pakhare, Abhijit P.; Gogia, Priya; Jain, Shikha; Gupta, Nayan; Goel, Sudhir K.; Malik, Rajesh (Frontiers in Pediatrics, 2020)
Background: The epidemic of obesity along with hypertension (HT) and cardiovascular disease is a growing contributor to global disease burden. It is postulated that obese children are predisposed to hypertension and subsequent cardiovascular disease in adulthood. Early detection and management of hypertension in these children can significantly modify the course of the disease. However, there is paucity of studies for characterization of blood pressure in obese children through ambulatory blood pressure monitoring (ABPM), especially in the developing world. This study aims to characterize ambulatory blood pressure in obese children along with calculation of cut offs for office BP that will predict ambulatory hypertension. Methods: In the present study, 55 children with body mass index (BMI) ≥95th percentile for age and sex were enrolled in a tertiary care hospital who underwent 24 hours ABPM and detailed biochemical investigations. Results: Ambulatory hypertension was recorded in 14/55 (25.5%; white coat hypertension in 17/29(58.6%)and masked hypertension in 2/26 (7.69)%. For office SBP percentile the area under curve (AUC) was 0.773 (95% CI: 0.619 to 0.926, p=0.005) and for office DBP percentile, the AUC was 0.802 (95% CI: 0.638 to 0.966, p=0.002). The optimal cut offs for office blood pressure which predicts ambulatory hypertension in obese children were 93rd percentile for systolic BP (sensitivity-67% and specificity -78%) and 88th percentile for diastolic BP (sensitivity-83% and specificity -62%). Conclusion: Ambulatory blood pressure abnormalities are highly prevalent among children with obesity. Office blood pressure did not optimally predict ambulatory hypertension. More than half of the children labelled as ‘hypertension’ on office blood pressure measurement in the study were diagnosed to have white coat hypertension (WCH), thus emphasizing the role of ABPM for evaluation of WCH before the child is subject to detailed investigations or started on pharmacotherapy